Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika Bertipe Higher Order Thinking Skills (HOTS) Berdasarkan Prosedur Newman - Meinita Eka Putri; Riza Agustiani; Harisman Nizar (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2021)
The weak ability of students in developing their reasoning power in solving mathematical problems, especially on HOTS questions causes students to have difficulty and experience many errors when solving them. The purpose of this study is to describe the errors made by students in solving HOTS-type math problems based on the Newman procedure. Subject taken from class IIB KMI and II C KMI Pondok Modern Daarul Abroor Banyuasin a total of 6 peopels who were selected besed on the results of the analysis of the previous semester to determine the initial abilitylevel using purposive Sampling Metod. Data collection techniques in the from of test question, interviews and documentation. Test the validity of the data using triangulation techniques. The data analysis technique used the Miles and Hubermen model in the from of (1) Analysis of students” previous semester scres, (2) Anaysis of stdent error in soving HOTS questions besed on the Newman procedur. The results of data analysis besed on the Newman procedure obtained were 0% reading errors, 29.2% problem understanding errors, 37.5% trnsformation errors, 74.2% process skills errors, 61% conclusion errors. The results of the intervew analysis showed that the factors causing studen errors were lack of interest in learning, students’ inaccurcy, lack of skills in solving HOTS questions, not nderstanding in operating calculations and not understanding concepts.